LIFE QUALITY AT WORK: importance of people in organizations - Pereira, Marriete Nagela; Trevelin, Ana Teresa Colenci (Revista Interface Tecnológica, 2020)
This article aimed to present and discuss that the issue of quality of life at work (QWL) is a motivational and strategic factor within organizations. The study sought to investigate the importance of quality of life in the organizational environment as a motivating aspect for workers and to present the importance of implementing quality of life at work programs as a strategy for improving productivity, in addition to emphasizing how these programs make organizations healthier, competitive and productive; also investigated which aspects associated with organizational behavior have a positive and negative impact on the health of the organization, and how the quality of life at work interferes with the company’s results, and promotes conditions that improve the development of its employees in the work environment. It was a qualitative, exploratory and descriptive research, which, through bibliographic research, sought to establish a comparison between different models on Quality of Life at Work and then present a Proposal for the Implementation of a Quality of Life at Work Program.